Sosialisasi Perilaku Hidup Bersih Sehat (PHBS) bersama Siswa Siswi SD Negeri Johorejo Kabupaten Kendal - Armita Zalfa Salsabila; Elis Sofiatun Nisah; Nurul Mafaza; M Rusydi Khairil Anwar; Rachmawati Choirotunnisa; Apriliana Drastisianti (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
PHBS in schools is a behaviour to empower students, teachers and the community in the school environment to apply and practice PHBS patterns in order to create a clean and healthy school environment. SD Negeri Johorejo Kendal District is one of the elementary schools located in Johorejo Village, Gemuh Subdistrict, Kendal District. This school rarely receives health counselling on PHBS.The purpose of the study was to increase the knowledge of the entire community in the school environment, especially students and teachers regarding the application of PHBS in the school environment and can practice how to wash hands with soap properly and brush teeth properly. This research uses a qualitative approach method. Based on the results of the study, it was found that there were four activities in the socialisation of PHBS at SD Negeri Johorejo, namely the explanation of material about what PHBS is and the benefits of PHBS, hand washing practice, and tooth brushing practice.